Role of Two Cell Wall Amidases in Septal Junction and Nanopore Formation in the Multicellular Cyanobacterium Anabaena sp. PCC 7120 - Bornikoel, Jan; Carrión, Alejandro; Fan, Qing; Flores, Enrique; Forchhammer, Karl; Mariscal, Vicente; Mullineaux, Conrad W.; Perez, Rebeca; Silber, Nadine; Wolk, C. Peter; Maldener, Iris (Frontiers in Cellular and Infection Microbiology, 2017)
Filamentous cyanobacteria have developed a strategy to perform incompatible processes in one filament by differentiating specialized cell types, N2-fixing heterocysts and CO2-fixing, photosynthetic, vegetative cells. These bacteria can be considered true multi-cellular organisms with cells exchanging metabolites and signaling molecules via septal junctions, involving the SepJ and FraCD proteins. Previously, it was shown that the cell wall lytic N-acetylmuramyl-L-alanine amidase, AmiC2, is essential for cell-cell communication in Nostoc punctiforme. This enzyme perforates the septal peptidoglycan creating an array of nanopores, which may be the framework for septal junction complexes. In Anabaena sp. PCC 7120, two homologs of AmiC2, encoded by amiC1 and amiC2, were identified and investigated in two different studies. Here, we compare the function of both AmiC proteins by characterizing different Anabaena amiC mutants, which was not possible in N. punctiforme, because there the amiC1 gene could not be inactivated. This study shows the different impact of each protein on nanopore array formation, the process of cell-cell communication, septal protein localization and heterocyst differentiation. Inactivation of either amidase resulted in significant reduction in nanopore count and in the rate of fluorescent tracer exchange between neighboring cells measured by FRAP analysis. In an amiC1 amiC2 double mutant, filament morphology was affected and heterocyst differentiation was abolished. Furthermore, the inactivation of amiC1 influenced SepJ localization and prevented the filament-fragmentation phenotype that is characteristic of sepJ or fraC fraD mutants. Our findings suggest that both amidases are to some extent redundant in their function, and describe a functional relationship of AmiC1 and septal proteins SepJ and FraCD.